Common EGFR-mutated subgroups (Del19/L858R) in advanced non-small-cell lung cancer: chasing better outcomes with tyrosine kinase inhibitors. (April 2015) - Reguart, Noemi; Remon, Jordi
ABSTRACT : Ten years ago, somatic mutations in EGFR were identified in patients with non-small-cell lung cancer. Demonstration of the antitumor efficacy of EGF receptor-directed tyrosine kinase inhibitors resulted in their approval for the treatment of advanced non-small-cell lung cancer. Insights into the role of EGFR -sensitizing mutations and acquired and de novo T790M resistance mutations followed, and differences in progression-free survival for patients with EGFR Del19- and L858R-mutated tumors treated with reversible first-generation EGF receptor tyrosine kinase inhibitors were reported. Recently, overall survival benefit in patients with Del19- but not L858R-mutated tumors has been demonstrated after treatment with afatinib, an irreversible ErbB family blocker. Although the biology underlying this difference in survival is currently unclear, this review examines several hypotheses.